Job demands, low back pain, and job crafting behaviors: a proposed framework - Al-Natour, Malek Ahmad; Abdullah, Nor Azimah Chew (2019)
The purpose of this paper is to propose a framework for understanding Job Crafting Behaviors (JCBs) as a proactive behavioral treatment in the relationship between Job Demands (JDs) and Low Back Pain (LBP). Though the relationship between JDs and LBP is well-established in the ergonomics literature, studies on the role of proactive behaviors are neglected. More so, while a few studies have examined behavioral treatment and its role in to JDs-LBP relationship, none has examined JCBs in relation to JDs-LBP relationship. Hence, this paper discusses JCBs as a moderator of the JDs (psychological and physical JDs)-LBP relationships. A conceptual model supported by Job Demands-Resources (JD-R) theory is thus proposed for future empirical studies and for expanding the JCBs and ergonomics literature.